Game design and control using EEG signals - Zhang, Yanxiang (2019)
With the blossom of the gaming industry, an increasing number of novel input devices are invented to provide unique experiences for the consumers. Among the devices, Brain-Computer Interface (BCI) is a new approach which is a system that allows direct communication using brain wave signal as Electroencephalogram (EEG) between human brain and computer machines. Based on researches worked on EEG, it has been proved that BCI control has a significant potential to enter the game market. In this project, existing BCI algorithms are reviewed and tested using a consumer-grade headset Muse, and a 2.5D pixel styled action game “8 ball monsters” is developed with an optimised EEG module to obtain user’s concentration through Muse. In addition to the development, the user acceptance tests (UAT) has been done with and without EEG headset to get the feedback of the game design as well as the experience using Muse headset.